Implementing the EU renewable target through green certificate markets - Finn Roar Aune; Hanne Marit Dalen; Cathrine Hagem (Statistics Norway, Research Department, 2010)
The EU Parliament has agreed on a target of a 20 % share of renewables in the EU's total energy consumption by 2020. To achieve the target, the Council has adopted mandatory differentiated national targets for each of the Member States. In this paper we consider the potential for cost reductions by allowing for trade in green certificates across Member States. We show that differentiated national targets cannot ensure a cost effective implementation of the overall target for EU's green energy consumption. Trade in green certificates can ensure a cost effective distribution of green energy production, but the national targets prevents a cost effective distribution of energy consumption. Nevertheless, our numerical model indicates that EU-wide trade in green certificates may cut the EU's total cost of fulfilling the renewable target by as much as 70 % compared to a situation with no trade. However, the design of green certificate markets may have large impact on the distribution of costs across countries.
Keywords: Q48; Q54; Q58; 330; Energy policy; green certificate markets; renewable targets